Validity of the Working Alliance Inventory (patient version) in adult systemic psychotherapy: Evidence from an experiment using the non-random change method - Prusiński, Tomasz (Przegląd Psychologiczny, 2021)
Aim The aim of this study was to verify the validity of the patient version of the Working Alliance Inventory (WAI-PC). Method The theoretical validity of the WAI-PC was experimentally estimated using the non-random change method proposed by Cronbach and Meehl. Results The results of the t-test showed significant differences between the experimental and control groups. Conclusion The study confirmed the validity of the WAI-PC as a tool for measuring alliance in adult psychotherapy.